Minding your business. (Bookseller, 2003)
The article presents information on the best of the forthcoming or recently published business and computer books, selected by four specialist booksellers James Lake, Sean Pratley, Martin Cox and Andrew Duffield. "The Art of Deception," by Kelvin Mitnick and William Simon, gives extraordinary real-life examples of cons, swindles and "social engineering" attacks on banks, businesses and government organizations and shows how easily firewalls and encryption protocols can be broken. "Beyond Fear: Thinking Sensibly About Security in an Uncertain World," by Bruce Schneier covers a series of current computer security topics. Some other books are "The Iron Triangle," by Dan Briody, "Goggle Hacks," by Tara Calishain and Rael Dornfest, "Adventure Capitalist," by Jim Rogers and others.